2017
DOI: 10.1002/pon.4597
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antiemetic‐induced akathisia in patients at a comprehensive cancer center

Abstract: Akathisia is an unpleasant feeling of motor restlessness with anxiety. Clinicians need to have a full understanding to identify the subtle difference between functional anxiety and akathisia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Rashid et al reported a 4.7% incidence of akathisia among patients taking antiemetic agents in a retrospective study in a tertiary cancer center. 20 A 2016 systematic review of antipsychotic-induced akathisia stated that a lack of studies with specific scales for evaluation, and patients with cancer and terminally ill patients in palliative care settings could be at higher risk for the development of akathisia as a side effect. 21 The objective of these above-mentioned studies was mainly akathisia, which was not diagnosed using a validated tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rashid et al reported a 4.7% incidence of akathisia among patients taking antiemetic agents in a retrospective study in a tertiary cancer center. 20 A 2016 systematic review of antipsychotic-induced akathisia stated that a lack of studies with specific scales for evaluation, and patients with cancer and terminally ill patients in palliative care settings could be at higher risk for the development of akathisia as a side effect. 21 The objective of these above-mentioned studies was mainly akathisia, which was not diagnosed using a validated tool.…”
Section: Discussionmentioning
confidence: 99%
“…Rashid et al reported a 4.7% incidence of akathisia among patients taking antiemetic agents in a retrospective study in a tertiary cancer center. 20…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are associated with the occurrence of psychological distress in patients with cancer. The National Comprehensive Cancer Network guideline on distress management (2017) has summarized the risk factors of psychological distress as: a) health-related risk factors, b) personal risk factors, c) spiritual, d) social factors, and e) other risk factors - sexual and physical abuse, substance use disorders, and other mental disorders 23 . Via a critical appraisal of the literature, it is evident that the categorization of the associated factors for psychological distress differs in each study based on a given psycho-social context.…”
Section: Introductionmentioning
confidence: 99%
“…Akathisia occurs in 4.7% of patients receiving older-generation antiemetics (metoclopramide and prochlorperazine); however, these are rarely used as frontline agents in current practice. 6 Trials that explored olanzapine as an appetite stimulant for cancer-related anorexia have used doses ranging from 2.5 mg once daily to a maximum of 5 mg once daily for 8-12 weeks but have not reported extrapyramidal symptoms. 7,8 However, in the phase I trial by Naing et al 9 (doses ranging from 2.5 mg to 20 mg once daily), one of 39 patients developed EPS at a dose of 20 mg once daily.…”
mentioning
confidence: 99%
“…Akathisia occurs in 4.7% of patients receiving older-generation antiemetics (metoclopramide and prochlorperazine); however, these are rarely used as frontline agents in current practice. 6…”
mentioning
confidence: 99%